2010
DOI: 10.1097/mpg.0b013e3181c992be
|View full text |Cite
|
Sign up to set email alerts
|

Novel Screening Assay Performance in Pediatric Celiac Disease and Adult Dermatitis Herpetiformis

Abstract: : The new IgA/IgG anti-tTG/DGP EIA screen was slightly more sensitive than IgA anti-tTG alone in pediatric CD. This novel screening assay may allow the current recommendation of measuring total serum IgA in suspected GSE patients to be eliminated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 27 publications
5
18
1
Order By: Relevance
“…The sensitivity of the new anti-GAF3X test exceeded that of the conventional anti-nGli assay by 27% and was even higher than that of the previously reported anti-DGP test in patients with DH. 22,23 Our results in patients with DH are comparable with those recently carried out in a large cohort of patients with childhood CD, where sensitivities of 84% and 96% were found by the IgA-and IgG-anti-GAF3X ELISA, respectively. 15 Importantly, IgA-and IgG-anti-GAF3X ELISA detected 7 of 10 IgA-anti-tTG-negative patients with DH, whereas only one patient showed tTG-but not GAF3X-specific antibodies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The sensitivity of the new anti-GAF3X test exceeded that of the conventional anti-nGli assay by 27% and was even higher than that of the previously reported anti-DGP test in patients with DH. 22,23 Our results in patients with DH are comparable with those recently carried out in a large cohort of patients with childhood CD, where sensitivities of 84% and 96% were found by the IgA-and IgG-anti-GAF3X ELISA, respectively. 15 Importantly, IgA-and IgG-anti-GAF3X ELISA detected 7 of 10 IgA-anti-tTG-negative patients with DH, whereas only one patient showed tTG-but not GAF3X-specific antibodies.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, conflicting results were obtained by the use of the anti-DGP ELISA for detecting gluten sensitivity in patients with DH. 22,23 Although Sugai et al 22 found IgA or IgG-anti-DGP antibodies in 78% of 18 patients with untreated DH, Jaskowski et al 23 reported sensitivities of only 46% and 61% by the IgA-and IgG-DGP screen in 80 patients with DH on a normal diet, respectively. The reasons for these discrepant outcomes in patients with DH are unclear, as both investigations used the same ELISA system.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In that study, as well as in ours, serology samples were analyzed prospectively in standard medical care as opposed to all of the earlier studies, which may be part of the explanation for the dramatic difference in results regarding DGP specificity. Earlier studies have concluded that DGP does not outperform tTG (not even in children younger than 2 years) (8,17), but that the combination of tTG and DGP has higher sensitivity than tTG alone (15), which is also in concordance with our findings. Some studies have suggested that DGP should be included as a complement to tTG in future diagnostic algorithms for CD (9)(10)(11), but monetary costs and unnecessary duodenal biopsies have hitherto not been investigated.…”
Section: Discussionsupporting
confidence: 93%
“…26 The tissue transglutaminase (tTG) was identified as the autoantigen prevalent in CD, 27 while in the DH, the predominant autoantigen is the epidermal transglutaminase (eTG). 26,28,29 Sardy et al 26 proposed that the DH pathogenesis consists of immune response of low avidity for tTG, resulting initially in silent CD, that with continued exposure to gliadin, leads to the development of populations of antibodies with high affinity to eTG for cross-reactivity, which manifests as DH. Moreover, as in CD, in which genetic predisposition is associated with the HLADQ2 (allelesDQA1 * 0501 and DQB1 *020) and HLA-DQ8 (DQA1 * 03 alleles and DQB1* 0302), DH presents similar genetic alterations.…”
Section: Discussionmentioning
confidence: 99%